New Quality of Leadership and Management in Tech Startups – Why Supporting Gender Equality Matters. A Case Study of the Project “Shesnnovation Academy” - Młodzińska-Granek, Agnieszka; Dziob-Zadworna, Agnieszka (Nowa jakość przywództwa i zarządzania w startupach technologicznych − dlaczego wspieranie równości płci ma znaczenie? Studium przypadku projektu „Shesnnovation Academy”, 2025)
Aim: This article analysed the problem of gender equality in tech startups. The main aim of the article was to show how important it is to support women founding their tech startups to enhance the demanded social change. Methodology: The methodological approach was based on the functional theory of change (Radcliffe--Brown, 1952, 1957), theory of planned behaviour (Ajzen, 1991) and the entrepreneurial event model (Shapero & Sokol, 1982) to show how institutionalised support creates a positive impact on the decisions made by women in technology industries. The research also focused on Project Management Institute standards to show how particular projects supporting women in technologies and innovations should be designed. Results: The collected results were considered in the category of change, in terms of the motivation for change, the benefits of change and the approach to being a leader understood as an agent of change. Implications and recommendations: It was discovered that programmes such as the Shesnnovation Academy, if well run, can bring on a change in mentality. The study showed that the current European Union programmes encourage the creation of such grassroots initiatives that have an impact on the local community. Originality/value: The research focused on gender equality in the framework of the SDGs (United Nations, 2015). Their main value was to show the impact of grassroots endeavors, supporting gender equality in the technological field, and on changing the perception of women themselves.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 2, s. 101-113